Male great bowerbirds create forced perspective illusions with consistently different individual quality - Kelley, Laura A. (National Academy of Sciences, 2012)
Males often produce elaborate displays that increase their attractiveness to females, and some species extend their displays to include structures or objects that are not part of their body. Such “extended phenotypes” may communicate information that cannot be transmitted by bodily signals or may provide a more reliable signal than bodily signals. However, it is unclear whether these signals are individually distinct and whether they are consistent over long periods of time. Male bowerbirds construct and decorate bowers that function in mate choice. Bower display courts constructed by male great bowerbirds (Ptilonorhynchus nuchalis) induce a visual illusion known as forced perspective for the female viewing the male’s display over the court, and the quality of illusion is associated with mating success. We improved the quality of the forced perspective to determine whether males maintained it at the new higher level, decreased the perspective quality back to its original value, or allowed it to decay at random over time. We found that the original perspective quality was actively recovered to individual original values within 3 d. We measured forced perspective over the course of one breeding season and compared the forced perspective of individual males between two successive breeding seasons. We found that differences in the quality of visual illusion among males were consistent within and between two breeding seasons. This suggests that forced perspective is actively and strongly maintained at a different level by each individual male.